Effect of Trigona Bee Propolis Extract in Duck Egg Yolk Tris Diluent on the Quality of Boer Goat Spermatozoa at 5°C - Adawiah, S; Zaenuri, Lalu; Sumadiasa, IWL (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aimed to determine the quality of Boer goat spermatozoa when stored at 5°C in a duck egg yolk-tris diluent supplemented with propolis extract. The material used was fresh semen collected from ±2-year-old Boer goats using an artificial vagina. This research employed a laboratory experimental method with a Completely Randomized Design (CRD), consisting of four propolis extract treatments: 0% (T0), 0.25% (T1), 0.5% (T2), and 1% (T3), with five replications. Observed variables included motility, viability, and abnormality. Observations were conducted every day at the same time. Data were analysed using Analysis of Variance (ANOVA) and subsequently tested with Duncan's multiple range test. The research results indicate that the best average sperm motility was found in T1, at 54.40±11.14%, followed by T0 at 41.00±12.36%, T2 at 40.40±11.76%, and T3 at 39.60±2.88%. The highest sperm viability was observed in T1, 58.40±6.06%, followed by T3, 49.20±4.65%, T2, 45.60±9.04%, and T0, 44.00±6.85%. The lowest sperm abnormality was found in T1, 4.60±1.87%, followed by T2, 6.00±1.87%, T3, 5.80±4.81%, and T0, 5.00±2.44%. In conclusion, among the four different diluents, the addition of 0.25% propolis extract in Tris-diluted egg yolk diluent showed the highest ability to maintain the quality of Boer goat spermatozoa for three days at a storage temperature of 5°C. Further studies are needed on the effects of different concentrations of propolis extract, various egg yolks, and different temperatures Contribution to Sustainable Development Goals (SDGs)SDG 2 (Zero Hunger)SDG 3 (Good Health and Well-being) SDG 12 (Responsible Consumption and Production)